2022
DOI: 10.1093/bjsopen/zrac002
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of discharge within 72 hours of major colorectal surgery: lessons learned after 5 years of institutional experience with the ERAS protocol

Abstract: Background Early postoperative discharge after colorectal surgery within the enhanced recovery after surgery (ERAS) guidelines has been demonstrated to be safe, although its applicability has not been universal. The primary aim of this study was to identify the predictors of early discharge and readiness for discharge in a study population. Methods Early discharge was defined as discharge occurring in 72 h or less after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…LOS may be a surrogate marker for both illness severity and occurrence of in‐hospital postoperative complications. The introduction of the Enhanced Recovery After Surgery (ERAS) protocol has markedly reduced LOS after surgery, and studies report that discharge after 48–72 h is safe and feasible in an ERAS setting [5, 32]. One study on US Medicare data, however, reported an increased risk of readmission in hospitals with LOS ≤ 4 days [33].…”
Section: Discussionmentioning
confidence: 99%
“…LOS may be a surrogate marker for both illness severity and occurrence of in‐hospital postoperative complications. The introduction of the Enhanced Recovery After Surgery (ERAS) protocol has markedly reduced LOS after surgery, and studies report that discharge after 48–72 h is safe and feasible in an ERAS setting [5, 32]. One study on US Medicare data, however, reported an increased risk of readmission in hospitals with LOS ≤ 4 days [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, these conditions may only be met 1-2 days post-surgery. In a study of 788 ERAS colorectal surgical patients, Biondi et al [28] compared 146 (18.5%) who were discharged within 72 hours post-surgery to the remaining patients. They reported that over 80% adherence to ERAS was a positive factor for early discharge.…”
Section: ) Discharge Criteriamentioning
confidence: 99%